Developing Time – Sense in History - Ojha, Seema s. (JOURNAL OF INDIAN EDUCATION, 2008)
An understanding of time and chronology is indispensable to the study of history, which is the record of change through times. But teaching time concepts and dates in isolation without the accompanying development of context of the dated events is of no significance. It is true that children’s sense of a period is largely shaped by visual images of individuals, clothing, homes or events. But development of time sense in students depends mostly on the kind of teaching and learning strategies we adopt while dealing a particular topic. This paper focuses on how graphical representations of time concept in the form of timelines, time charts help students develop a sense of time and chronology.